1997
DOI: 10.1080/08923649709526949
|View full text |Cite
|
Sign up to set email alerts
|

The impact of remote‐site group size on student satisfaction and relative performance in interactive telecourses1

Abstract: Undergraduate college students in seventeen live, interactive telecourses at sixty-eight remote sites were asked to report their satisfaction with various facets of their telecourses, as well as their overall satisfaction with the courses. In addition, an index of relative performance was calculated for each student in which achievement in the current telecourse was compared to prior overall academic achievement. Results showed that remote-site group size (i.e., the number of individuals taking a course at a g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0
5

Year Published

1999
1999
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(41 citation statements)
references
References 12 publications
2
34
0
5
Order By: Relevance
“…Shneiderman, Borkowski, Alavi and Norman (1998) found that ODL students were highly satisfied with their experiences and indicated that they would take another distance education course. In a study of 288 undergraduate college students in distance education classes at remote sites, students reported overall satisfaction with the courses (Biner, Welsh, Barone, Summers & Dean, 1997). The authors further confirmed the contention that remote-site group size affects both the satisfaction and motivation of students enrolled in distance education, college-level courses-larger classes were associated with more negative student attitudes and lower levels of relative performance.…”
Section: Literature Reviewsupporting
confidence: 67%
“…Shneiderman, Borkowski, Alavi and Norman (1998) found that ODL students were highly satisfied with their experiences and indicated that they would take another distance education course. In a study of 288 undergraduate college students in distance education classes at remote sites, students reported overall satisfaction with the courses (Biner, Welsh, Barone, Summers & Dean, 1997). The authors further confirmed the contention that remote-site group size affects both the satisfaction and motivation of students enrolled in distance education, college-level courses-larger classes were associated with more negative student attitudes and lower levels of relative performance.…”
Section: Literature Reviewsupporting
confidence: 67%
“…15 Also, when the number of students at a distance site is closer to the number of students at the hosting site, student opinions of the course are more favorable. 16 Because we grouped all the distant-site students into 1 section, the ratio of host students to distant students was reduced from approximately 14:1 to 4:1 in that class. In addition to preferring the small class format, students preferred discussion sessions that were well structured as opposed to unstructured.…”
Section: Discussionmentioning
confidence: 99%
“…Course grades are often used as an indicator of student achievement in online instruction (Barnard, Paton, & Lan, 2008;Reinhart & Schneider, 2001;Noel-Levitz, 2011). But affective factors can be as important as cognitive factors in explaining and predicting student learning in online settings (Biner et al, 1997). Among the attitudinal constructs, student satisfaction, referring to student perceptions of learning experiences and perceived value of a course, may be particularly worthy of investigation.…”
Section: Literature Review Student Satisfactionmentioning
confidence: 99%
“…Nearly one third of higher education students enrolled in at least one online course (Allen & Seaman, 2008;Allen & Seaman, 2010). According to previous studies, online learning does not differ considerably from traditional face-to-face classroom learning in terms of learning outcomes (Allen & Seaman, 2010;Allen, Bourhis, Burrell & Mabry, 2002;Biner, Bink, Huffman & Dean, 1997;Brown & Liedholm, 2002;Johnson, 2000). Student satisfaction in online learning remains undiminished when compared to face-to-face instruction (Allen & Seaman, 2010).…”
Section: Introductionmentioning
confidence: 99%